PENEGAKAN HUKUM TERHADAP PELAKU PELANGGARAN LALU LINTAS AKIBAT KELALAIAN YANG MENGAKIBATKAN KEMATIAN (Studi Putusan Nomor: 241/Pid.sus/2018/PN.Mdn) - Samuel Manik; Aulia Rosa Nasution; Arie Kartika (ARBITER: Jurnal Ilmiah Magister Hukum, 2022)
Traffic violations cannot be left alone because based on available data most of the occurrence of traffic accidents are caused by the human factor of road users who do not comply with traffic regulations but there are still many causes outside of human factors such as broken tires, failed brakes, roads holes and so on. The problems in this study are criminal threats against traffic violations due to negligence resulting in the death of others, what factors cause negligence in traffic accidents that result in other people's death and law enforcement efforts against traffic offenders due to negligence causing death.The research method uses a type of empirical normative law. The nature of the research used is descriptive analysis. Data collection techniques using library research and field studies. Data analysis used qualitative analysis.The results of the study that the cause of negligence in traffic accidents that resulted in other people's death in the form of human negligence factors, inappropriate vehicle factors resulting in accidents, weather factors could not determine it then the road factor where it was damaged there would be many traffic accidents. Law enforcement provided in the form of preventive or preventive and repressive. The conclusion that the criminal threat to traffic violations due to negligence resulting in the death of another person is regulated in Article 359 of the Criminal Code for a maximum imprisonment of five years or a maximum confinement of one year and criminal sanctions are regulated in Article 310 Paragraph (4) of Law No. 22 of 2009 concerning Road Traffic and Transportation is a criminal offense for 6 (six) years. Factors that cause negligence in traffic accidents that cause other people to die are human factors, vehicle factors, weather factors, and road factors. Efforts to enforce the law against traffic violations due to negligence causing death, one of which is prevention and repressive efforts.